2010
DOI: 10.3892/ijmm_00000537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omeprazole on the expression of transcription factors in osteoclasts and osteoblasts

Abstract: Abstract. The use of proton pump inhibitors (PPIs) seems to be related to increased fracture risk but the mechanism is unclear. In an effort to clarify the mechanism, we evaluated the effect of omeprazole, a representative of the PPIs, on the expression of transcription factors in osteoclasts and osteoblasts. Murine RAW264.7 and MC3T3-E1 cells were used for osteoclast and osteoblast analysis, to which various concentrations of omeprazole were added. RAW264.7 cells with ≥3 nuclei were considered tartrate-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Therefore, the inhibitory effect of PPIs on ALP activity opens up the possibility of decreased mineralization, an effect that was observed in the present study. More recently, a study performed in murine MC3T3-E1 cells [21] showed that omeprazole, at 10 À5 M, increased the expression of osteocalcin and the osteoprotegerin/RANKL ratio, suggesting positive effects on osteoblastic behavior, and also the possibility of an indirect negative effect on osteoclastic differentiation mediated by osteoblastic cells [17]. In the present study, PPIs negatively affected human osteoblastic cells, but, as the cell culture systems were quite different, direct comparison is difficult.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Therefore, the inhibitory effect of PPIs on ALP activity opens up the possibility of decreased mineralization, an effect that was observed in the present study. More recently, a study performed in murine MC3T3-E1 cells [21] showed that omeprazole, at 10 À5 M, increased the expression of osteocalcin and the osteoprotegerin/RANKL ratio, suggesting positive effects on osteoblastic behavior, and also the possibility of an indirect negative effect on osteoclastic differentiation mediated by osteoblastic cells [17]. In the present study, PPIs negatively affected human osteoblastic cells, but, as the cell culture systems were quite different, direct comparison is difficult.…”
mentioning
confidence: 53%
“…This observation suggests that PPIs might induce direct nonspecific cytoxicity, which is further increased by specific inhibitory effects on selected functional parameters, namely osteoclastic resorption activity and the osteoblastic ability to form a mineralized matrix. It is worth noting that differential effects of PPIs on proliferation and functional parameters were also reported by Hyun et al ., who showed that, at ~ 10 −5 m , omeprazole did not interfere with cell viability/proliferation but affected osteoclastic and osteoblastic gene expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Karsdal et al [22] demonstrated that the selective proton pump blocker bafilomycin completely inhibits osteoclastic bone resorption and even increases the number of osteoclasts. Also, Hyun et al [23] showed that the PPI omeprazole significantly increases the OPG/RANKL ratio without affecting TRAP positivity. This is in line with the results of the present study, demonstrating a pantoprazoleinduced increase of the OPG/RANKL ratio without affecting the number of TRAP-positive osteoclasts.…”
Section: Discussionmentioning
confidence: 97%
“…Pig IL-6 and IL-8 mRNA transcripts in PK15 cells were quantitatively measured by real-time PCR analyses as previously described (Hyun et al, 2010). The primer sequences used for each PCR are described in Table S1.…”
Section: Quantification Of the Interaction Between Rgs16 And Pcv2mentioning
confidence: 99%